Digging out the keys in the heap of seized pangolin scales: up scaling pangolin conservation using wildlife forensics. (June 2021) - Priyambada, Prajnashree; Jabin, Gul; Singh, Abhishek; Ghosh, Avijit; Singh, Sujeet Kumar; Chatterjee, Moitrye; Venkatraman, Chinnadurai; Chandra, Kailash; Sharma, Lalit Kumar; Thakur, Mukesh
Abstract: Pangolins, despite banned through legislative measures, are threatened by heavy illegal poaching for the demand of meat and scales in the making of Traditional East Asian Medicines (TEAM), resulting in severe decline of the population sizes across the distribution range. Species assignment from the confiscated scales is pre-requisite to enforce the appropriate national and international law and legislations in the successful prosecution of the cases in the court of law. In the present study, we characterised the morphological features in voucher specimens of the Indian pangolin ( Manis crassicaudata) and Chinese pangolin ( Manis pentadactyla) and used the identified keys to establish the species identity from the confiscated scales. We investigated intra and inter genetic variations by sequencing 624 scales of pangolin for cytb gene and obtained unique haplotypes to Indian and Chinese pangolins by comparing sequences with all eight pangolin species. Scales from the voucher specimens, which varied in the size, shape and weight, were measured for morphological features to establish species signature of Indian and Chinese pangolins. The cumulative success of species assignment using morphological features from the confiscated scales was 98.33% and 100% from the large and caudal scales, respectively. The present study has generated reference signature of Indian and Chinese pangolins from the scales and facilitates the law enforcements for taking spot decision by ascertaining species identity from the seized scales. Highlights: Pangolins, most trafficked mammal in the world, extensively used in Traditional East Asian Medicines. We developed morphological keys from the confiscated scales for species discrimination of Indian and Chinese pangolins. The developed keys will facilitate law enforcements for taking spot decision and use the finding in legal proceedings.